Agent-based parallel system for numerical computations - Sieniek, Marcin; Gurgul, Piotr; Kołodziejczyk, Pawel; Paszyński, Maciej (Procedia computer science, 2010)
The paper describes a way of applying agent paradigm to hp-adaptive Finite Element Method (hp-FEM). We discuss a choice of classical numerical algorithms suitable for incorporating into an agent-based application, along with an efficient way of adopting them into an agent-based application. We define formally a Computing Multi Agent System (C-MAS) for adaptive 1D FEM based on Smart Solid Agent model and describe tasks executed by hp-FEM agents. Finally, we spare a few paragraphs for numerical experiments performed with an application developed accordingly to the described model.